Divergence Between Clinical Trial Evidence and Actual Practice in Use of Dual Antiplatelet Therapy After Transient Ischemic Attack and Minor Stroke. Issue 5 (23rd March 2023) - De Matteis, Eleonora; De Santis, Federico; Ornello, Raffaele; Censori, Bruno; Puglisi, Valentina; Vinciguerra, Luisa; Giossi, Alessia; Di Viesti, Pietro; Inchingolo, Vincenzo; Fratta, Giovanni Matteo; Diomedi, Marina; Bagnato, Maria Rosaria; et al.
Abstract : Background: Randomized controlled trials (RCTs) proved that short-term (21–90 days) dual antiplatelet therapy (DAPT) reduces the risk of early ischemic recurrences after a noncardioembolic minor stroke or high-risk transient ischemic attack (TIA) without substantially increasing the hemorrhagic risk. We aimed at understanding whether and how real-world use of DAPT differs from RCTs. Methods: READAPT (Real-Life Study on Short-Term Dual Antiplatelet Treatment in Patients With Ischemic Stroke or TIA) is a prospective cohort study including >18-year-old patients treated with DAPT after a noncardioembolic minor ischemic stroke or high-risk TIA from 51 Italian centers. The study comprises a 90-day follow-up from symptom onset. In the present work, we reported descriptive statistics of baseline data of patients recruited up to July 31, 2022, and proportions of patients who would have been excluded from RCTs. We compared categorical data through the χ² test. Results: We evaluated 1070 patients, who had 72 (interquartile range, 62–79) years median age, were mostly Caucasian (1045; 97.7%), and were men (711; 66.4%). Among the 726 (67.9%) patients with ischemic stroke, 226 (31.1%) did not meet the RCT inclusion criteria because of National Institutes of Health Stroke Scale score >3 and 50 (6.9%) because of National Institutes of Health Stroke Scale score >5. Among the 344 (32.1%) patients with TIA, 69 (19.7%) did not meet the RCT criteria because of age, blood pressure, clinical features, duration of TIA, presence of diabetes score <4 and 252 (74.7%) because of age, blood pressure, clinical features, duration of TIA, presence of diabetes score <6 and no symptomatic arterial stenosis. Additionally, 144 (13.5%) patients would have been excluded because of revascularization procedures. Three hundred forty-five patients (32.2%) did not follow the RCT procedures because of late (>24 hours) DAPT initiation; 776 (72.5%) and 676 (63.2%) patients did not take loading doses of aspirin and clopidogrel, respectively. Overall, 84 (7.8%) patients met the RCT inclusion/exclusion criteria. Conclusions: The real-world use of DAPT is broader than RCTs. Most patients did not meet the RCT criteria because of the severity of ischemic stroke, lower risk of TIA, late DAPT start, or lack of antiplatelet loading dose. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT05476081.